Data for Modelling and Analysis of Induction Preheating of Moving Filler Wire in Wire-Based Directed Energy Deposition - Cao, Ruofeng; Sun, Yongle; Suder, Wojciech; Chen, Xin; Li, Zhiyong; Williams, Stewart W. (Cranfield University, 2026)
Induction preheating of filler wire is a novel technique that allows precise control of wire temperature before melting by main energy source in a wire-based Directed Energy Deposition (wire-DED). This which can enhance deposition rate and reduce defects. This study investigates the evolution of electromagnetic and thermal fields during induction heating in a moving filler wire through a coil. An electromagnetic-thermal model was developed to determine the magnetic flux, eddy current, temperature, and energy absorption efficiency. A multiphysics model was validated by experiments under diverse process conditions. The model allows understanding of electromagnetic-thermal mechanism for the transient and steady-state distributions of the wire temperature. In the steady state, the peak temperature is located immediately outside the coil exit end of the inductor coil, and the temperature gradient across the wire diameter is marginal. The sensitivity analysis to establish most important parameters was carried out This study demonstrates an effective modelling approach to induction heating of moving wire and provides critical insights for designing and optimising the induction coil and process for preheating of wires for additive manufacturing and other similar manufacturing processes (e.g. welding and cladding).
Temperature; relative magnetic permeability electrical conductivity density heat capacity at constant pressure; thermal conductivity; wire feed speed; wire feed length; current; frequency wire diameter; radial distance; coupling distance; Coil-wire diameter; coil pitch; coil turn; power; energy density magnetic field intensity magnetic flux; current density; skin depth
Keywords: Induction heating; electromagnetic field; wire feeding; multiphysics model; parametric sensitivity; additive manufacturing